Caring for the Most Vulnerable: A Model for Managing Maladaptive Behavior in Children with Mental Special Needs During the COVID-19 Pandemic - ARMAN, AYŞE (MARY ANN LIEBERT, INC, 2021)
Background: This article presents the results of a comprehensive national model developed for managing maladaptive behaviors (MBs) in children with mental special needs (CMSNs) during the coronavirus disease 2019 (COVID-19) pandemic that combines telehealth-based Applied Behavioral Analyses, psychiatric interventions, and support from local psychosocial teams. This study aims to determine the effectiveness of a system that combined telehealth applications with local psychosocial support teams, allowing services from video calls to emergency interventions. Materials and Methods: The system combines the telehealth applications with the services from local psychosocial intervention teams. In addition to system records covering sociodemographic variables and initial complaints, a telephone survey questioning the effectiveness and satisfaction of the system was used as the main outcome. Results: In total, 347 individuals used the system with mothers constituting the majority of applicants (88.7%, n = 332). The overall satisfaction of the system was 8.8/10. In terms of effectiveness, 63.3% (n = 237) of caregivers reported an improvement in the reason of application. Counselors decided on a need for follow-up visits for 36.6% (n = 137) of applications. A referral to a psychiatrist was asked for 40 patients (10.6%). Discussion: To our best knowledge, this is the first study presenting a model for managing MBs of CMSNs during the COVID-19 outbreak. In general, therefore, it seems that there is a need for unique systems to handle behavioral problems of CMSNs. Conclusions: The findings of this study suggest that it is possible to establish an integrative multistep multidisciplinary telehealth-based approach in a short while.
Keywords: behavioral health; COVID-19 pandemic; children with special needs; INTELLECTUAL DISABILITY; PRESCHOOL-CHILDREN; YOUNG-PEOPLE; ADOLESCENTS; DISASTER; STRESS